ANALISIS LAPORAN KEUANGAN DAN KUALITAS PELAYANAN PADA RUMAH SAKIT UMUM DAERAH (RSUD) PANGKEP - Hasrianti Hasrianti; Amril Amril; Sitti Zulaiha (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
This research aims to be first, to measure and analyze the level of efficiency achieved by the Pangkep Regional General Hospital (RSUD). The calculation technique used in the study is to calculate the efficiency ratio Regional General Hospital (RSUD) Pangkep. Second, by calculating the quality of service provided by the Regional General Hospital (RSUD) Pangkep through Servqual Score by using five-dimensional variables Tangibles, Reliability, Responsiveness, Assurance, and Empathy, namely by comparing the reality received with the expected patient with the five dimensions. Based on the results of the calculation and data collection of the Regional General Hospital (RSUD) budget realization report, it can be concluded that the management of Pangkep Regional General Hospital (RSUD) is not good because the efficiency level above 100% means that financial management is said to be not good. As for the quality of service provided from five dimensions based on patient responses are classified as no quality and no effective.